Proposed method of identification of technical errors in artistic gymnastic - Leandro, C.; Avila-Carvalho, L.; Sierra-Palmeiro, E.; Bobo-Arce, M. (Science of Gymnastics Journal, 2016)
The primary aim of this study was to analyse all technical elements used in the Rhythmic Gymnastics Kiev World Championship 2013, and identify the Structural characteristics of the technical content of elite Rhythmic Gymnastics individual routines. The data has been collected from the difficulty forms concerning 288 individual routines. To allow the comparison between gymnasts with different levels the individual routines were clustered into 3 subgroups according to their final ranking competition. Body difficulty elements were organized, according to the composition requirements stated in the RG Code of Points (FIG, 2012). Non-parametric tests - Kruskal-Wallis, Mann-Whitney and Friedman test were applied to determine whether there were significant differences between groups. As main results we can point out that in general the rhythmic gymnasts used similar body difficulties with limited variety. The highest valued elements are Dynamic Elements with Rotation and throw (DER) and rotations and these represent 50% of the total value of the routine. Concerning the dance steps and mastery, no differences were found between the routines of gymnasts place in the three parts of the ranking. The routines had differences in the composition pattern between the gymnasts according to the final ranking of the gymnasts in following items: (i) on the number of rotations of flat foot or other part of the body, Fouetté rotations and Mixed Difficulties; (ii) on the value of jumps, rotations, DER and Mixed Difficulties.